Contract Learning as Individualized Instructional Strategies in Improving Students’ Performance in Academic Writing Courses - Sumarsono, Dedi; Permana, Dira (JOLLT Journal of Languages and Language Teaching, 2023)
The use of contract learning is essential to involve students actively in the classroom activities and to facilitate teachersâ€™ control and flexibility in the teaching and learning process, while letting students to work on activities independently. Therefore, this research is aimed at 1) revealing out whether or not contract learning instruction has a significant difference in the studentsâ€™ academic writing performance; 2) describing to what extent the contract learning promotes studentsâ€™ learning and autonomy; and 3) elaborating how the students perceive the diagnostic and feedback phases of individualized strategy as embedded in the contract learning. This study is mixed method interventional research design because the data are obtained from quantitative and qualitative. The participants of the study was the year 3 students of English Department at Mandalika University of Education consisting of 21 students. The instruments used in collecting the data are diagnostic test of academic writing performance, contract form, and questionnaires. The quantitative data are analyzed through the inferential paired t-test. Meanwhile, the qualitative data of each individualâ€™s response to each item on the questionnaire are broken down according to the responses to each question, and the responses are compared, contrasted, and explored to find patterns and themes. The results revealed that 1) contract learning has affected positively studentsâ€™ learning and performance in academic writing, 2) contract learning brings positive improvement on academic writing performance and 3) positive Â perception towards the application of contract learning was shown by the students as it provided self-study materials and multiple types of feedback from theÂ the lecturer. This implies that students may benefit from multiple types of feedback and that instructorsâ€™ expertise in effective feedback delivery is of paramount importance.